Effects of endometriosis on sleep quality of women: does life style factor make a difference? - Samaneh Youseflu; Shahideh Jahanian Sadatmahalleh; Ghazall Roshanzadeh; Azadeh Mottaghi; Anoshirvan Kazemnejad; Ashraf Moini (BMC, 2020)
Abstract Background This study aimed to compare the lifestyle factors and SQ between women with and without endometriosis. Also in this essay, the influence of food intake, socio-demographic and clinical characteristics on sleep quality of women with endometriosis was determined. Methods Of the 156 infertile women approached for the study, 78 women had endometriosis and 78 were included in the control group. At first, each participant completed a checklist including questions about demographics, physical activity, reproductive and menstrual status. SQ was assessed by the Pittsburgh Sleep Quality Index (PSQI). Dietary data were collected using a validated 147-item semi-quantitative FFQ. Results Irregular menstrual status, menorrhagia, dysmenorrhea, pelvic pain, history of abortion, family history of endometriosis were associated with endometriosis risk (P < 0.05). In women with physical activity more than 3 h per week, high consumption of the dairy product, and fruit endometriosis is less common (P < 0.05). The total PSQI score, and the scores for subjective sleep quality, sleep latency, sleep disturbance domains were significantly different between the two groups (P < 0.05). In women with endometriosis, poor SQ was associated with dysmenorrhea, pelvic pain, dyspareunia, physical activity, and low consumption of the dairy product, fruit, and nut (p < 0.05). Conclusion In endometriosis women, SQ was lower than healthy individuals. Lifestyle factors can effect on SQ of these patients.